Language Assessment Practices and Beliefs: Implications for Language Assessment Literacy - Frank Giraldo (HOW)
This study reports the contextual Language Assessment Literacy (LAL) of five Colombian English language teachers. Two semi-structured interviews and reflective journals were used for data collection. The findings show that the teachers used varied traditional and alternative assessment instruments, assessed language and non-language constructs, used assessment information to improve teaching and learning, evaluated assessment results, and engaged students in quantitative peer assessment. As for beliefs, data show that students’ success and failure in assessment were connected to past experiences, and that assessment was appropriate given a number of features. Participants’ answers about LAL show a complex and multifaceted construct. Taken together, the findings serve as baseline data to further professional development in language assessment.